Using MongoDB with Node.js : storing data as documents - Higbee, Wes; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"Using MongoDB with Node.js is the fourth title in Wes Higbee's explanation of all things Node. This course details how to store data - as documents - coming from your JavaScript apps into MongoDB. There are two popular approaches to interacting with MongoDB: The native driver and Mongoose. In this video, you'll learn about both of these, when to pick one over the other, and something else equally important (and often neglected): How to write maintainable asynchronous MongoDB communications code. Web app developers with a strong command of JavaScript, those wanting to incorporate server-side programming into their development, and those wanting to better understand NoSQL database technology will appreciate this step-by-step guide to using MongoDB with Node.js."--Resource description page.
Presenter, Wes Higbee.
Title from title screen (viewed May 5, 2016).
Date of publication from resource description page.
Keywords: Node.js.; MongoDB; Web applications; Electronic books